Protection Works Against Wave Attacks In The Haor Areas Of Bangladesh: Analysis Of Sustainability - Alam, M.K.; Hasan, MD.R. (Penerbit Universiti Sains Malaysia, 2010)
Haor is the local name of the saucer-shaped, naturally depressed areas of Bangladesh. There are 414 haors in the northeast region that comprise approximately 17% of the country. These areas are submerged under deep water from July to November due to the overflow of rivers and heavy rainfall, causing them to appear like seas with erosive waves. Recently, the wave attack has drastically increased because of de-plantation and changing cropping patterns to allow for more agricultural production. The local people, government and Non-Government Organisations (NGOs) have tried many techniques to protect life and property against wave attacks. A cost comparison shows that Cement Concrete (CC) blocks over geotextile on the slope embankment is a cost-effective, environment friendly and socially acceptable method to prevent loss of life and property. However, the design rules employed by the engineers are faulty because there is knowledge gap in the application of wave hydraulics among these professionals. As a result, damage frequently occurs and maintenance costs are increasing. This study explores the sustainability of the CC blocks used in the Haor areas by evaluating two case studies with the verification of available design rules.